Clock controls angiogenesis - Jensen, Lasse Dahl (Landes Bioscience, 2013)
Circadian rhythms control multiple physiological and pathological processes, including embryonic development in mammals and development of various human diseases. We have recently, in a developing zebrafish embryonic model, discovered that the circadian oscillation controls developmental angiogenesis. Disruption of crucial circadian regulatory genes, including Bmal1 and Period2, results in marked impairment or enhancement of vascular development in zebrafish. At the molecular level, we show that the circadian regulator Bmal1 directly targets the promoter region of the vegf gene in zebrafish, leading to an elevated expression of VEGF. These findings can reasonably be extended to developmental angiogenesis in mammals and even pathological angiogenesis in humans. Thus, our findings, for the first time, shed new light on mechanisms that underlie circadian clock-regulated angiogenesis.